Genetics of resistance in bread wheat cultivars HD 2687, HD 2501, HW 2004, UP 2425 and RAJ 3765 to leaf rust - K.V. PRABHU; RAM CHARAN, A. ABBASSI MOGHADDM*, P. BAHADUR (Indian Phytopathology, 2004)
Wheat cultivars HD 2687, HD 2501, HW 2004, UP 2425 and RAJ 3765 were genetically analyzed with three pathotypes 0R9 (106), 109R31-1 (77-2) and 17R23 (104) of leaf rust pathogen. Segregation of F2 seedlings suggested three dominant independent genes for resistance in HD 2687, one dominant gene for resistance each in HD 2501 and HW 2004 and two dominant independent genes each in UP 2425 and RAJ 3765 against Pathotype 0R9 (106). Analysis of reciprocal crosses, BC1 and BC2 of above cultivars confirmed the above findings. The gene Lr23 in HD 2687; Lr23 and Lr26 in UP 2425; Lr23 and Lr34 in HD 2501; Lr24 in HW 2004 and Lr13 in RAJ 3765 were validated based on pedigree and ITs of cultivars.